2007
DOI: 10.1007/s00203-007-0295-9
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bacillus anthracis spores prepared under various environmental conditions

Abstract: Bacillus anthracis makes highly stable, heat-resistant spores which remain viable for decades. Effect of various stress conditions on sporulation in B. anthracis was studied in nutrient-deprived and sporulation medium adjusted to various pH and temperatures. The results revealed that sporulation efficiency was dependent on conditions prevailing during sporulation. Sporulation occurred earlier in culture sporulating at alkaline pH or in PBS than control. Spores formed in PBS were highly sensitive towards spore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 31 publications
2
41
1
Order By: Relevance
“…The wide variations observed in the thermal inactivation pattern of spores of B. cereus could be attributed to one or more of the following (1) characteristics of strains of B. cereus with environmentally induced resistance due to dipicolinic acid content, degree of hydration and mineral content (Marquis and Shin 1994;Palop et al 1996;Mazas et al 1999b;Melly et al 2002;Baweja et al 2008), (2) temperatures which have induced spore formation as well as other conditions prevailing during sporulation (Condon et al 1992;Baweja et al 2008) and (3) heterogeneity in the cluster of spores with respect to germination and/or survival (Byrne et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide variations observed in the thermal inactivation pattern of spores of B. cereus could be attributed to one or more of the following (1) characteristics of strains of B. cereus with environmentally induced resistance due to dipicolinic acid content, degree of hydration and mineral content (Marquis and Shin 1994;Palop et al 1996;Mazas et al 1999b;Melly et al 2002;Baweja et al 2008), (2) temperatures which have induced spore formation as well as other conditions prevailing during sporulation (Condon et al 1992;Baweja et al 2008) and (3) heterogeneity in the cluster of spores with respect to germination and/or survival (Byrne et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, spores, which are formed from the same vegetative cells, achieve resistance to heat processing. This resistance is invariably attributed to a metabolically inactive complex of nucleic acids and calcium dipicolinic acid formed under a set of prevailing unfavourable conditions (Murrel 1988;Nicholson et al 2000;Baweja et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, spores of B. anthracis developed in nutrient deprived conditions submerged in PBS, displayed lower resistance properties against wet heat and several chemical denaturants, such as acidic or alkali pH and hydrogen peroxide. These spores contained the same level of DPA as the spores from the control culture but may have an altered composition due to lack of precursors for synthesis of different spore components (Baweja et al 2008). Similarly, in our study there was no correlation found between the heat resistance of spores derived from different conditions and their DPA content measured according to (Kort et al 2005) (not shown).…”
Section: Discussionsupporting
confidence: 47%
“…Ryu and Beuchat (2005) exposed biofilms of B. cereus formed in TSB to air which resulted in increased spore formation at 22 °C and high relative humidity of 97 and 100 %, whereas exposure to air with low humidity (85%) did not affect sporulation but resulted in death of vegetative cells. Baweja et al (2008) transferred planktonic early stationary culture of Bacillus anthracis into PBS and observed significantly increased sporulation efficiency up to 50% compared to 5% for the control within 8 h, confirming the sporulation promoting effect of nutrient deprivation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation